AVALIAÇÃO DA QUALIDADE DE FRUTOS DE MARACUJAZEIRO NAS CONDIÇÕES EDAFOCLIMÁTICAS DO ECÓTONO CERRADO – PANTANAL - Fernandes, Carla; De Castro, Adriana; Mello, Ana Caroline; Da Costa, Simone Angélica; Soares, Giovana; Da Silva, Maiele (ANAIS DO ENIC, 2018)
-